Toxicity of malathion against two strains of the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) - Faruki, SI (University Journal of Zoology, Rajshahi University, 2007)
Key words: Malathion; T. castaneum; mortality; growth; development; fecundity; fertility Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 5-9